Educational direction of STEM in the system of realization of blended teaching of physics - Oleksandr O. Martyniuk; Oleksandr S. Martyniuk; Serhii Pankevych; Ivan Muzyka (Academy of Cognitive and Natural Sciences, 2021)
Today's requirements for the training of specialists encourage the modernization of education through the introduction of new educational technologies, in particular the introduction of STEM (Science, Technology, Engineering and Mathematics). The article analyzes the aspects of the concept of STEM implementation in the educational sector of Ukraine. The analysis of scientific works on the development of STEM education allowed to establish the features of teaching physics, taking into account current trends in education. The components of STEM teaching of physics include means of blended learning in combination with cloud-based technologies. This concept is especially relevant in the context of the COVID-19 pandemic. Seven models of blended learning, which are the most common in educational practice in Ukraine, are analyzed. The concepts of compositional combination of full-scale experiment with the use of digital laboratories, cloud services and BYOD (Bring Your Own Device) technologies as tools for the implementation of blended learning in the STEM system are outlined. Guided by the recommendations of the state program to improve the quality of natural and mathematical education, the emphasis is on the use of modern experimental tools and digital laboratories. The use of digital laboratories makes it possible to organize a physical experiment at a fundamentally new level. An example of a complex study of mechanics using a digital laboratory, cloud services and BYOD technology is given. The results of the pedagogical experiment convincingly prove that the technologies of blended learning with the use of cloud services and BYOD tools are a powerful tool in the work of teachers.